2007
DOI: 10.1007/s00464-006-9143-2
|View full text |Cite
|
Sign up to set email alerts
|

Electrothermal bipolar vessel sealing device vs. ultrasonic coagulating shears in laparoscopic colectomies: a comparative study

Abstract: In our laparoscopic colorectal experience, EBVS Ligasure has proven safe and effective in vessel sealing. Patients in whom this device was used had less blood loss and slight advantages in operating time and postoperative hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
64
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(68 citation statements)
references
References 13 publications
4
64
0
Order By: Relevance
“…Differences between the two reviewers were resolved by reexamination of the original article until consensus was attained about the study's data. This process yielded five papers [18][19][20][21][22] comparing the efficacy of EBVS and UE in terms of operative time and intraoperative blood loss in laparoscopic colorectal surgery. All the studies were read in their entirety to assess their appropriateness for inclusion in the metaanalysis.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Differences between the two reviewers were resolved by reexamination of the original article until consensus was attained about the study's data. This process yielded five papers [18][19][20][21][22] comparing the efficacy of EBVS and UE in terms of operative time and intraoperative blood loss in laparoscopic colorectal surgery. All the studies were read in their entirety to assess their appropriateness for inclusion in the metaanalysis.…”
Section: Methodsmentioning
confidence: 99%
“…Five studies [18][19][20][21][22] comparing EBVS with UE and fulfilling the inclusion criteria were identified ( Table 1). The trial of Hubner et al [20] was excluded from the final analysis because it provided inadequate data for statistical analysis.…”
Section: Characteristics Of the Trialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most data are derived from laparoscopic colon surgery, where it has been shown that high-energy power sources specifically adapted for endoscopic surgery reduce operative time and blood loss [66][67][68][69]. These data can be transferred to laparoscopic rectal cancer surgery.…”
Section: (100% [Strong Consensus]; Gor C: 100% [Strong Consensus])mentioning
confidence: 99%